(untitled) (Palíndromo, 2021)
The Article Through detail the grotesque concept around Fine Arts that pass by the cultural renaissance, we will analyse how the grotesque of renaissance reshapes itself in the rock musical genre, not only in the musical speech, but verbal and visual through case studies. The research objective is to understand why the grotesque, a aesthetic genre that comes from the visual poetic, lies present and constantly in a reconfiguration process on the daily contemporary art, with emphasis on rock musical genre. Our methodology will be based on case studies and our theoretical foundation will be integrated by the authors CARROL (1999); KAYZER (2013); SODRÉ and PAIVA (2003); Victor Hugo (2014), authors who will stablish theories, foundations and concepts against or study grotesque aesthetics and also horror.